Review: Philo and Paul among the Sophists: Alexandrian and Corinthian Responses to a Julio-Claudian Movement (2nd edn) - Oakes, Peter (Journal of Semitic studies, 2004)
Philo and Paul among the Sophists: Alexandrian and Corinthian Responses to a Julio-Claudian Movement (2nd edn) Bruce W. Winter , Wm. B. Eerdmans, Grand Rapids 2002. xix + 302. Price: $32.00/£22.99 paperback. ISBN: 0-8028-3977-0